Feminist Theology A Reader - Loades, Ann; Mary Daly; Elisabeth Schussler Fiorenca; Ursula King; Phyllis Trible; Rosemary Radford Ruether (London ; Louiseville,Ky. Westminster/John Knox Press, 1990)
This timely selection of readings represents the work of some of the best and most influential writers the Christian feminist movement has produced--both in Britain and America. With its helpful introduction and editorial commentary it will be warmly welc
Keywords: Feminist theology